Cyberprzemoc a kreowanie własnego wizerunku w internecie - co w ich mechanizmach zmienia niepełnosprawność młodych dorosłych osób? - Plichta, Piotr; Barlińska, Julia; Pyżalski, Jacek (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Today's media have an important impact on young peoples’ social life - transforming many social and developmental aspects. Online activity of young adults not only increases the availability to positive and educational experiences, but also arises the exposure to online threats. The main scope of this article is exploring the role of appearance and social practices concerning its creation in the process of peer cyberbullying among Polish young adults (N=329). Online body autopresentation has been found an important factor moderating the process of online aggression. The dissemination of beliefs was also examined – assessment of own attractiveness, the apprehension of the appearance assessment by others and the scale of activities focused on editing and improving the appearance depicted in the pictures posted on social websites. The differences in these areas were examined between people with disabilities or those who have injuries or specific health conditions that affect their appearance and other young people.The results have revealed that particular research and intervention focus should be put on young people having a condition or injury affecting appearance and/or having a disability or serious health problems as this group has been found more prone to be victimized (regarding traditional bullying as well as cyberbullying).